Investigations of Fatigue Strength of Sandwich Plates - S. Ochelski; R. Gieleta; A. Kiczko (Engineering Transactions, 2003)
The results of investigations of mechanical properties of the polyvinyl chloride foam and the epoxide composite reinforced by glass clothes and their fatigue life are presented. The fatigue life and the dependence of the structure degradation on the number of cycles of the sandwich plate subject to bending are also given. The plate was composed with the core made of the polyvinyl chloride foam and the face sheets of the epoxide composite reinforced by glass clothes.